New Group 5 and 6 transition metal imido complexes with monodeprotonated triazacyclononane ligands - Fletcher, J; Male, N; Wilson, P; Rees, L; Mountford, P; Schroder, M (2000)
The l,4-dialkyl-l,4,7-triazacyclononanes HR. The Royal Society of Chemistry 2000.